Effects of low molecular weight organic acids on adsorption of Cd(II) by Auricularia auricula spent substrate-derived biochar: Types and reaction sequence - Xuesheng Liu; Yue Jiang; Wei Yang; Sha Li; Yu Jin; Juanjuan Qu; Wei Wang (Environmental Chemistry and Ecotoxicology)
Cadmium (Cd) is one of the most mobile and toxic heavy metals that seriously deteriorates crop quality and threatens human health. It is considered an effective means to stabilize Cd in soil and reduce plant uptake by the application of biochar. However, the interactions and mechanisms between biochar and Cd in the rhizospheric soil are blurred due to the involvement of low molecular weight organic acids (LMWOAs). In this study, four different reaction sequences were established to simulate the chemical interactions between LMWOAs and cadmium (Cd) in the rhizospheric soil with biochar. In terms of adsorption patterns, the results show that, LMWOAs not only slow down the adsorption of Cd ions onto biochar, but also desorb the adsorbed Cd ions from biochar. Tartaric acid (TA) makes adsorption easier, while citric acid (CA) and malic acid (MA) make it more difficult. In terms of adsorption mechanism, the functional groups of MA and CA on biochar the vary wtih reaction sequence, thereby affecting the Cd adsorption onto biochar. The functional groups of TA participate in the adsorption to the greatest extent, and its impact on adsorption is rarely influenced by the reaction sequence. The reaction sequence does not affect the types of Cd-crystals, but affects dissolvement or attachment to the surface of biochar. This study provides chemical insights for further understanding the impact of LMWOAs on the interaction between biochar and heavy metals in soil.